A single column two-phase mixed mode monolithic material, its preparation method and application

CN118681540BActive Publication Date: 2026-10-27HEBEI UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410725225.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-06
Publication Date
2026-10-27
Estimated Expiration
2044-06-06

AI Technical Summary

Technical Problem

但是松针中的成分复杂多样,目前的研究尚未阐明松针中能够治疗类风湿性关节炎的具体成分

Benefits of technology

本发明制备得到的单柱两相混合模式整体材料具有比单一模式整体材料更优越的分离能力,并具有良好的渗透性和机械强度,其可应用于松针中抗类风湿性关节炎的活性成分的分离和筛选,制备方法简单,经济实用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004878413930000011
    Figure HDA0004878413930000011
  • Figure HDA0004878413930000012
    Figure HDA0004878413930000012
  • Figure HDA0004878413930000013
    Figure HDA0004878413930000013
Patent Text Reader

Abstract

The application belongs to the field of separation and screening of effective chemical components in pine needles, and provides a single-column two-phase mixed mode monolithic material, a preparation method and application thereof, the preparation method of the single-column two-phase mixed mode monolithic material comprises the following steps: respectively preparing a hydrophilic prepolymer solution and a hydrophobic prepolymer solution; adding the hydrophilic prepolymer solution and the hydrophobic prepolymer solution into the same stainless steel empty column tube to obtain a mixed mode monolithic material. The single-column two-phase mixed mode monolithic material prepared by the method has good mechanical strength and permeability, and the active components in pine needles against rheumatoid arthritis can be separated and screened by using the single-column two-phase polymer monolithic material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a monolithic column for separating and screening effective chemical components in pine needles, specifically a monolithic material in a single-column two-phase hybrid mode, its preparation method, and its application. Background Technology

[0002] High-performance liquid chromatography (HPLC), a widely used method for compound separation and analysis, has shown limitations in handling complex sample systems due to its reliance on a single stationary phase. The introduction of mixed-mode HPLC effectively overcomes these limitations. Mixed-mode chromatography integrates multiple separation mechanisms within a single column, achieving effective separation of sample components. Because it integrates multiple separation mechanisms, mixed-mode columns offer superior selectivity, column capacity, and resolution compared to single-mode columns, and can replace multiple dedicated columns, reducing material waste.

[0003] However, the analysis of complex samples places increasingly higher demands on separation science. Pine needles, the needle-like leaves of pine trees (Pinaceae family), are a traditional Chinese medicine with effects such as dispelling wind and dampness, killing insects and relieving itching, promoting blood circulation and calming the mind. Pine needle extracts contain abundant active substances, and their therapeutic effects on rheumatoid arthritis have been recorded in ancient herbal texts. Modern medical books also record their function of dispelling wind and promoting blood circulation, used to treat rheumatic joint pain. However, the components of pine needles are complex and diverse, and current research has not yet elucidated the specific components in pine needles that can treat rheumatoid arthritis. Therefore, given the lack of clarity regarding the active components in pine needles for treating rheumatoid arthritis, finding a simple and efficient method to separate and screen them is one of the important challenges currently facing researchers. Summary of the Invention

[0004] The purpose of this invention is to provide a monolithic material in a single-column two-phase hybrid mode and its preparation method, and to apply it to the separation and screening of active ingredients in pine needles that have anti-rheumatoid arthritis properties.

[0005] This invention first provides a method for preparing a monolithic material in a single-column two-phase hybrid mode, comprising the following steps: (1) Azobisisobutyronitrile, acrylamide, pentaerythritol triacrylate and isopropanol are mixed sequentially and ultrasonically vibrated to obtain a hydrophilic prepolymer solution; (2) Azobisisobutyronitrile, N-hydroxymethylacrylamide, N-isopropylacrylamide, ethylene glycol dimethacrylate, n-butanol and isopropanol are mixed sequentially and then subjected to ultrasonic oscillation to obtain a hydrophobic prepolymer solution. (3) First, pour the hydrophilic prepolymer into a stainless steel hollow tube with one end sealed and the other end open; then pour the hydrophobic prepolymer into the same stainless steel hollow tube; seal the open end of the stainless steel hollow tube, and bathe it in a water bath at 55-65℃ for 10-11 hours. Take out the single-column two-phase mixed mode integral material after rinsing. The monolithic material of the single-column two-phase hybrid mode is used to separate and screen the active ingredients in pine needles that are effective against rheumatoid arthritis.

[0006] Furthermore, the ratio of azobisisobutyronitrile, acrylamide, pentaerythritol triacrylate and isopropanol used in step (1) is 0.008-0.01 g : 0.01-0.02 g : 0.25-0.3 mL : 1.7 mL.

[0007] Furthermore, in step (2), the ratio of azobisisobutyronitrile, N-hydroxymethylacrylamide, N-isopropylacrylamide, ethylene glycol dimethacrylate, n-butanol and isopropanol is 0.008-0.01g: 0.05-0.06g: 0.6-0.075g: 0.25ml: 0.9mL: 0.9mL.

[0008] Furthermore, the ultrasonic oscillation time in steps (1) and (2) is 20-30 min.

[0009] Furthermore, in step (3), the volume ratio of the hydrophilic prepolymer and the hydrophobic prepolymer is 1:1.

[0010] Furthermore, the rinsing in step (4) involves connecting the empty stainless steel column after the water bath to a high-performance liquid chromatography (HPLC) system, using 100% methanol as the mobile phase, and rinsing at a flow rate of 1 mL / min for 1.5 h. Its purpose is to remove unreacted soluble components, such as pore-forming agents.

[0011] The present invention also provides a monolithic material in a single-column two-phase hybrid mode prepared by the above method.

[0012] The present invention also provides a method for separating and screening active ingredients in pine needles that have anti-rheumatoid arthritis properties. The method involves using the above-mentioned single-column two-phase mixed mode integral material as a solid-phase extraction adsorbent, coupled with high-performance liquid chromatography, to separate and screen the active ingredients in pine needles that have anti-rheumatoid arthritis properties.

[0013] Furthermore, in the above method, firstly, the monolithic material of the single-column two-phase mixed mode is connected to a high-performance liquid chromatograph, and water is used as the mobile phase to enrich the pine needle extract. Then, 60% acetonitrile aqueous solution is used as the mobile phase to perform preliminary separation of the chemical components in the pine needle extract retained on the monolithic material during enrichment, and the preliminary separation eluent is collected. The preliminary separation eluent is further separated by a reversed-phase semi-preparative column, and the eluent with an elution time of 11-14 min is collected. Then, it is separated by a normal-phase semi-preparative column to obtain different parts of the eluent.

[0014] Furthermore, in the above method, the active ingredients in pine needles that have anti-rheumatoid arthritis properties are screened by detecting the effects of the separated eluent on RAW264.7 cell viability, RAW264.7 cell inflammatory factors, and NO production by RAW264.7 cells.

[0015] The beneficial effects of this invention are as follows: The monolithic material prepared by this invention has superior separation ability compared to monolithic materials with a single-mode structure, and also has good permeability and mechanical strength. It can be applied to the separation and screening of active ingredients in pine needles that are effective against rheumatoid arthritis. The preparation method is simple, economical and practical. Attached Figure Description

[0016] Figure 1 Electron micrographs of the hydrophilic monolithic material (A) in Example 1 and the hydrophobic monolithic material (B) in Example 4.

[0017] Figure 2 This section describes the effect of the eluent obtained from the initial separation on the viability of RAW264.7 cells under different mobile phase conditions in Example 8. The control group consisted of RAW264.7 cells that were not subjected to any intervention. "Enrichment" refers to the portion of the eluent collected when the pine needle extract was passed through the mixed-mode whole material with water as the enrichment mobile phase. "50% acetonitrile", "60% acetonitrile", "70% acetonitrile" and "80% acetonitrile" refer to the portions of the eluent collected when the portion enriched and retained on the whole material with water as the enrichment mobile phase was eluted with 50% acetonitrile aqueous solution, 60% acetonitrile aqueous solution, 70% acetonitrile aqueous solution and 80% acetonitrile aqueous solution, respectively, after enrichment with water.

[0018] Figure 3This example illustrates the effect of the eluent obtained from preliminary separation on the inflammatory factors IL-6 (A) and TNF-α (B) in RAW264.7 cells under different mobile phase conditions in Example 9. The blank group consisted of RAW264.7 cells without any intervention, and the control group consisted of RAW264.7 cells stimulated only with lipopolysaccharide. "Extraction" refers to the aqueous extract of pine needles. The definitions of "enrichment," "50% acetonitrile," "60% acetonitrile," "70% acetonitrile," and "80% acetonitrile" are the same as in Example 9. Figure 2 .

[0019] Figure 4 This example illustrates the effect of the eluent obtained from preliminary separation on NO production in RAW264.7 cells under different mobile phase conditions in Example 10. The definitions of blank group, control group, extraction, enrichment, and "50% acetonitrile," "60% acetonitrile," "70% acetonitrile," and "80% acetonitrile" are the same as in Example 10. Figure 3 .

[0020] Figure 5 Chromatograms (A) of the eluent from the "60% acetonitrile" fraction separated by the reversed-phase semi-preparative column and (B) of the eluent from the "60% acetonitrile (1)" fraction separated by the normal-phase semi-preparative column are shown.

[0021] Figure 6 The effect of the eluent further separated in Example 12 on the viability of RAW264.7 cells.

[0022] Figure 7 The effect of the eluent further separated in Example 13 on the inflammatory factors IL-6 (A) and TNF-α (B) of RAW264.7 cells.

[0023] Figure 8 The effect of the eluent further separated in Example 14 on NO production in RAW264.7 cells. Detailed Implementation

[0024] The following examples are provided to further illustrate the present invention, but are not intended to limit the invention in any way.

[0025] Example 1: Preparation of hydrophilic monolithic material 1 Accurately weigh 0.01 g of azobisisobutyronitrile (AIBN) and 0.02 g of acrylamide, add 0.25 mL of pentaerythritol triacrylate and 1.7 mL of isopropanol, and sonicate for 30 min to dissolve and disperse. After sonication until homogeneous, pack the mixture into a stainless steel hollow column and react in a 60℃ water bath for 10 h to obtain the hydrophilic monolithic material 1. The subsequent rinsing process involves connecting the water-bathed monolithic material to a high-performance liquid chromatography (HPLC) system, using 100% methanol as the mobile phase, and slowly and uniformly increasing the flow rate to 1 mL / min for 90 min to flush out pore-forming agents such as isopropanol. The column back pressure of the hydrophilic monolithic material 1 was measured to be 1.1 MPa. Its microstructure was observed using a scanning electron microscope as follows: Figure 1 As shown in Figure A, the specific surface area of ​​the hydrophilic monolithic material 1, measured using a specific surface area meter, is 29.9273 m². 2 / g.

[0026] Example 2: Preparation of hydrophilic monolithic material 2 Under the same conditions as in Example 1, 0.01 g of azobisisobutyronitrile (AIBN), 0.02 g of acrylamide, 0.2 mL of pentaerythritol triacrylate, and 1.7 mL of isopropanol were added and sonicated for 30 min to dissolve and disperse them. After sonication until homogeneous, the mixture was placed in a stainless steel hollow column and reacted in a 60°C water bath for 10 h to obtain the hydrophilic monolithic material 2. The subsequent rinsing process was the same as in Example 1. Monolithic material 2 was washed out during the rinsing process and could not be used for subsequent experiments. This indicates that the mechanical strength of the monolithic material decreased due to the reduction of the crosslinking agent pentaerythritol triacrylate.

[0027] Example 3: Preparation of hydrophilic monolithic material 3 Under the same conditions as in Example 1, 0.01 g of azobisisobutyronitrile (AIBN), 0.02 g of acrylamide, 0.25 mL of pentaerythritol triacrylate, and 1.5 mL of isopropanol were added and sonicated for 30 min to dissolve and disperse them. After sonication until homogeneous, the mixture was loaded into a stainless steel hollow column and reacted in a 60°C water bath for 10 h to obtain the hydrophilic monolithic material 3. The subsequent rinsing process was the same as in Example 1. The back pressure of monolithic material 3 was measured to be 1.4 MPa. Due to the reduction of the pore-forming agent isopropanol, the column back pressure of this monolithic material increased, and the permeability decreased. The high column back pressure will have an adverse effect on the entire liquid phase system, and the monolithic material will also face the risk of collapse.

[0028] Example 4: Preparation of Hydrophobic Monolithic Material 1 Accurately weigh 0.01 g of azobisisobutyronitrile, 0.05 g of N-hydroxymethylacrylamide, and 0.075 g of N-isopropylacrylamide. Add 0.25 mL of ethylene glycol dimethacrylate, 0.9 mL of n-butanol, and 0.9 mL of isopropanol, and sonicate for 30 min to dissolve and disperse. After sonication until homogeneous, pack the mixture into a stainless steel hollow column and react in a 60°C water bath for 10 h to obtain hydrophobic monolithic material 1. Subsequent rinsing procedures are as described in Example 1. The column back pressure of this hydrophobic monolithic material 1 was measured to be 0.8 MPa. Its microstructure was observed using a scanning electron microscope as shown below. Figure 1 As shown in Figure B, the specific surface area of ​​the hydrophobic monolithic material 1, measured using a specific surface area meter, is 138.7411 m². 2 / g.

[0029] Example 5: Preparation of Hydrophobic Monolithic Material 2 Under the same conditions as in Example 4, 0.01 g of azobisisobutyronitrile, 0.05 g of N-hydroxymethylacrylamide, and 0.075 g of N-isopropylacrylamide were added to 0.2 mL of ethylene glycol dimethacrylate, 0.9 mL of n-butanol, and 0.9 mL of isopropanol, and dissolved and dispersed by sonication for 30 min. After sonication until homogeneous, the mixture was placed in a stainless steel hollow column and reacted in a 60°C water bath for 10 h to obtain the final product. The subsequent rinsing process was the same as in Example 1. The monolithic material was washed out during the rinsing process and could not be used for subsequent experiments. This indicates that a reduction in the crosslinking agent ethylene glycol dimethacrylate resulted in a decrease in the mechanical strength of the monolithic material.

[0030] Example 6: Preparation of hydrophobic monolithic material 3 Under the same conditions as in Example 4, 0.01 g of azobisisobutyronitrile, 0.05 g of N-hydroxymethylacrylamide, and 0.075 g of N-isopropylacrylamide were added to 0.25 mL of ethylene glycol dimethacrylate, 0.8 mL of n-butanol, and 0.8 mL of isopropanol, and dissolved and dispersed by sonication for 30 min. After sonication until homogeneous, the mixture was loaded into a stainless steel hollow column and reacted in a 60°C water bath for 10 h to obtain the final product. The subsequent rinsing process was the same as in Example 1. The column back pressure of the monolithic material was measured to be 1.1 MPa. Due to the reduction of the pore-forming agents n-butanol and isopropanol, the column back pressure of the monolithic material increased, and the permeability decreased.

[0031] Example 7: Preparation of Monolithic Materials in a Single-Column Two-Phase Hybrid Mode Preparation of hydrophilic prepolymer: Accurately weigh 0.01 g azobisisobutyronitrile, 0.02 g acrylamide, add 0.25 mL pentaerythritol triacrylate and 1.7 mL isopropanol, and add them to a clean centrifuge tube (No. 1) in sequence. Sonicate for 30 min to dissolve and disperse.

[0032] Preparation of hydrophobic prepolymer: Accurately weigh 0.01 g azobisisobutyronitrile, 0.05 g N-hydroxymethylacrylamide, and 0.075 g N-isopropylacrylamide, add 0.25 mL ethylene glycol dimethacrylate, 0.9 mL n-butanol, and 0.9 mL isopropanol, and then add them sequentially to another clean centrifuge tube (No. 2). Sonicate for 30 min to dissolve and disperse.

[0033] First, the hydrophilic prepolymer solution was poured into a stainless steel hollow tube sealed at one end. Next, the hydrophobic prepolymer solution was poured in. The other end of the stainless steel hollow tube was then sealed, and the tube was placed in a water bath at 60°C for 10 hours. Subsequent rinsing was performed as in Example 1.

[0034] Example 8: Effect of the preliminarily separated eluent on the viability of RAW264.7 cells The monolithic material prepared in Example 7 using a single-column two-phase hybrid mode was connected to a high-performance liquid chromatograph (HPLC). First, water was used as the mobile phase to enrich the pine needle extract. Then, using 50%, 60%, 70%, and 80% acetonitrile aqueous solutions as mobile phases, the chemical components retained in the pine needle extract on the monolithic material during enrichment were separated. The eluents were collected, and after evaporation from each mobile phase, the eluents were reconstituted with culture medium and used for cell experiments. The CCK-8 assay was used to evaluate the potential impact of the pine needle eluents on the viability of RAW264.7 cells.

[0035] The effect of pine needle eluent on the viability of RAW264.7 cells was as follows: Figure 2 As shown, the survival rate of RAW264.7 cells in each experimental group exceeded 80% compared to the untreated control group. This means that the pine needle extract did not have a negative impact on cell survival, indicating that the pine needle eluent had no significant effect on the cell viability of the RAW264.7 cell line.

[0036] Example 9: Effects of the preliminarily separated eluent on inflammatory factors in RAW264.7 cells The chemical components in the pine needle extract were initially separated, following the same procedures as in Example 8. The pine needle eluates obtained under different mobile phase conditions were evaporated to dryness and then reconstituted with culture medium. These solutions were then used to incubate the RAW264.7 cell line for 2 hours. Lipopolysaccharide was added to the culture medium to a final concentration of 200 ng / mL, and the RAW264.7 cells were cultured under this stimulation for another 24 hours. After culture, the supernatant of the RAW264.7 cells was collected, and cell residues and impurities were removed by centrifugation. To analyze the cytokines that RAW264.7 cells may release during this process under the action of different eluates, enzyme-linked immunosorbent assay (ELISA) was used to detect the supernatant. Figure 3 As shown, the fraction obtained after water enrichment of pine needle extract and elution with acetonitrile / water (60 / 40, V / V) as the mobile phase effectively reduced the inflammatory marker IL-6 produced by lipopolysaccharide-induced RAW264.7 cells. Figure 3 A) and TNF-α ( Figure 3 B) is superior to the components obtained under other conditions.

[0037] Example 10: Effect of the initially separated eluent on NO production in RAW264.7 cells The NO content in the supernatant of RAW264.7 cells from different groups obtained in Example 9 was detected using a NO detection kit. The detection results are as follows: Figure 4 As shown, the fraction obtained after enriching the pine needle extract with water and eluting with acetonitrile / water (60 / 40, V / V) as the mobile phase can significantly reduce the NO level in the lipopolysaccharide-induced RAW264.7 cell line. The results under this condition are better than those under other conditions.

[0038] Example 11: Further separation of pine needle eluent First, the pine needle extract was enriched using water as the mobile phase. Then, using 60% acetonitrile aqueous solution as the mobile phase, the chemical components retained in the pine needle extract during enrichment were initially separated, and the preliminary eluent was collected. The pine needle eluent obtained from the preliminary separation was then further separated using a reversed-phase semi-preparative column to obtain different fractions of the eluent. The chromatogram of the pine needle eluent separated by the reversed-phase semi-preparative column is shown below. Figure 5As shown in Figure A, the eluent is roughly divided into two parts. The eluents with elution times of 11-14 min and 14-17 min were collected respectively and labeled "60B (1)" and "60B (2)". The eluents of "60B (1)" and "60B (2)" were dried, concentrated, and reconstituted with water, respectively, and then separated using a normal-phase semi-preparative column to obtain different portions of the eluent. The eluents were then dried, concentrated, and reconstituted. The chromatogram of the eluent of "60B (1)" separated by the normal-phase semi-preparative column is shown below. Figure 5 B. It can be seen that the eluent of the “60B (1)” section achieved good separation and was divided into four parts, which were denoted as “normal phase 1”, “normal phase 2”, “normal phase 3” and “normal phase 4” respectively. However, the eluent of the “60B (2)” section could not achieve good separation on the chromatographic column.

[0039] Effect of further separated eluent on RAW264.7 cell viability in Example 12 The eluents from the four fractions "positive phase 1," "positive phase 2," "positive phase 3," and "positive phase 4" obtained in Example 11 were used to evaluate the potential impact of pine needle eluent on RAW264.7 cell viability using the CCK-8 assay. The results are as follows: Figure 6 As shown, the survival rate of RAW264.7 cells in each experimental group was more than 80% higher than that of the untreated control group, indicating that the elution solutions of the four phases "phase 1", "phase 2", "phase 3" and "phase 4" did not have a negative impact on the survival of RAW264.7 cells, that is, the pine needle elution solution had no significant effect on the cell viability of the RAW264.7 cell line.

[0040] Example 13: Effects of further isolated eluent on inflammatory factors in RAW264.7 cells The eluents from the four fractions "positive phase 1," "positive phase 2," "positive phase 3," and "positive phase 4" obtained in Example 11 were used to culture RAW264.7 cell lines according to the method in Example 9. The supernatant of the RAW264.7 cell culture medium was collected, and enzyme-linked immunosorbent assay (ELISA) was used to detect the inflammatory factors of RAW264.7 cells in the supernatant. The detection results are as follows: Figure 7 As shown, the elution buffer of the "positive phase 1" portion can significantly reduce the synthesis of lipopolysaccharide-induced inflammatory cytokines IL-6 (Figure A) and TNF-α (Figure B) in the RAW264.7 cell line, and the results under this condition are better than those under other conditions.

[0041] Example 14: Effect of further separated eluent on NO production in RAW264.7 cells The NO content in the cell supernatant obtained in Example 13 was detected using a NO detection kit. The detection results are as follows: Figure 8As shown, the elution buffer from the "positive phase 1" section can significantly reduce the NO level in the lipopolysaccharide-induced RAW264.7 cell line, and the results under this condition are better than those under other conditions.

[0042] In conclusion, it can be inferred that the eluent from the "positive phase 1" fraction contains a high level of active ingredients in pine needles that have anti-rheumatoid arthritis properties.

Claims

1. A method for preparing a monolithic material with a single-column two-phase hybrid mode, characterized in that, Includes the following steps: (1) Azobisisobutyronitrile, acrylamide, pentaerythritol triacrylate and isopropanol are mixed sequentially and ultrasonically vibrated to obtain a hydrophilic prepolymer solution; (2) Azobisisobutyronitrile, N-hydroxymethylacrylamide, N-isopropylacrylamide, ethylene glycol dimethacrylate, n-butanol and isopropanol are mixed sequentially and then subjected to ultrasonic oscillation to obtain a hydrophobic prepolymer solution. (3) First, pour the hydrophilic prepolymer into a stainless steel hollow tube with one end sealed and the other end open; then pour the hydrophobic prepolymer into the same stainless steel hollow tube; seal the open end of the stainless steel hollow tube, and bathe it in a water bath at 55-65℃ for 10-11 hours. Take out the single-column two-phase mixed mode integral material after rinsing. The monolithic material of the single-column two-phase hybrid mode is used to separate and screen the active ingredients in pine needles that are effective against rheumatoid arthritis. The ratio of azobisisobutyronitrile, acrylamide, pentaerythritol triacrylate and isopropanol used in step (1) is 0.008-0.01 g : 0.01-0.02 g : 0.25-0.3 mL : 1.7 mL; The ratio of azobisisobutyronitrile, N-hydroxymethylacrylamide, N-isopropylacrylamide, ethylene glycol dimethacrylate, n-butanol and isopropanol in step (2) is 0.008-0.01g: 0.05-0.06g: 0.6-0.075g: 0.25ml: 0.9mL: 0.9mL.

2. The method for preparing a monolithic material in a single-column two-phase hybrid mode according to claim 1, characterized in that, The ultrasonic oscillation time in steps (1) and (2) is 20-30 min.

3. The method for preparing a monolithic material in a single-column two-phase hybrid mode according to claim 1, characterized in that, In step (3), the volume ratio of the hydrophilic prepolymer and the hydrophobic prepolymer is 1:

1.

4. The method for preparing a monolithic material in a single-column two-phase hybrid mode according to claim 1, characterized in that, The rinsing in step (3) involves connecting the empty stainless steel column after the water bath to the high-performance liquid chromatography system, using 100% methanol as the mobile phase, and rinsing for 1.5 h at a flow rate of 1 mL / min.

5. The monolithic material of a single-column two-phase hybrid mode prepared by the preparation method according to any one of claims 1-4.

6. A method for separating and screening active ingredients from pine needles that combat rheumatoid arthritis, characterized in that, Using the monolithic material of the single-column two-phase hybrid mode described in claim 5 as a solid-phase extraction adsorbent, coupled with high-performance liquid chromatography, the active ingredients in pine needles that combat rheumatoid arthritis were separated and screened.

7. The method according to claim 6, characterized in that, First, the monolithic material in single-column two-phase mixed mode was connected to a high-performance liquid chromatograph, and water was used as the mobile phase to enrich the pine needle extract. Then, 60% acetonitrile aqueous solution was used as the mobile phase to perform preliminary separation of the chemical components in the pine needle extract retained on the monolithic material during enrichment, and the preliminary separation eluent was collected. The initially separated eluent was further separated by passing it through a reversed-phase semi-preparative column. The eluent with an elution time of 11-14 min was collected and then separated by passing it through a normal-phase semi-preparative column to obtain different fractions of the eluent.

8. The method according to claim 7, characterized in that, The active ingredients in pine needles for anti-rheumatoid arthritis were screened by detecting the effects of the separated eluent on RAW264.7 cell viability, RAW264.7 cell inflammatory factors, and NO production by RAW264.7 cells.

Citation Information

Patent Citations

  • Application of ultrasound in intelligent controlled release of medicament coated by temperature sensitive material

    CN102319434A

  • Preparation method of organic polymer solid phase extraction material and application thereof

    CN105294932A